DNS blocking in IQ: pornhub.com, twitter.com, xvideos.com (Iraq) - Voidly (2026)
CRITICAL severity censorship detected in Iraq. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: IQ-2026-0003
Keywords: censorship; IQ; censorship; critical